A far greater sense of community: The impact of volunteer behaviour on the wellness of rural older Australians. (November 2017) - Warburton, Jeni; Winterton, Rachel
Abstract: This paper builds on place-based research investigating the transformative potential of volunteering for service-deprived, ageing rural communities. Here, we critically explore the relationship between communities of place, voluntarism and wellness for rural older Australians. We draw on data from a large qualitative multi-site study, and utilise Ryan et al.'s (2005) systemic model of community attachment. Findings support the dual perspective of strong community sentiments through social embeddedness in rural communities; and personal interests, associated with rational choice theory, through healthy ageing practices. Both aspects have demonstrated positive impact on wellness, but also risks to wellness associated with over-expectations of volunteers. Highlights: Volunteering has health benefits for both rural volunteers and local older people. Rural voluntarism is associated with a solidarity of community sentiments. It is also a rational choice through solidarity of interests in healthy ageing. Both aspects are critical to rural older people's wellness. But there are also risks to wellness posed by over-reliance on volunteers.